Exposure to Radioactive Emanations of Medical Personnel in Percutaneous Nephrolithotomy - E. Sierra-Diaz; E. Gaxiola-Perez; C. Beas-Ruiz Velasco; I. Sedano-Portillo; C. A. Gonzalez-Gonzalez; M. Adel-Dominguez; F. Davila-Radilla (SAGE Publishing, 2018)
The use of radioactive emanations has been of great importance for the performance of endourology procedures, such as percutaneous nephrolithotomy (NLP). The damage to health caused by radiation has been a sensitive issue. The objective of this work was to determine the dose received by the surgeon during NLP and the total dose generated by the fluoroscope. A cross-sectional study was conducted with data from a cohort study with a duration of 18 months that included 101 patients. Radiation was measured with dosimeter during the last 6 months. During the last 6 months of the study, 34 patients were submitted to surgery. The average age was 47 years. Average fluoroscopy time was 58.3 second (24-122 seconds) in both male and female groups, with 57.16 seconds and 58.95 seconds per case, respectively ( P = .6). Radiation emitted during 6 months for the 34 patients was 330.5 mGy. The total radiation measured by the dosimeter was 1 mSv, which is equivalent to 0.3% of the total radiation applied during the procedures. Doses measured by the dosimeter on the surgeon were within the recommended annual doses although dose received by the hands exceeds the authorized limits (500 mSv/y).